Endoplasmic Reticulum Stress and Tumor Microenvironment in Bladder Cancer: The Missing Link - Nie, Zhenyu; Chen, Mei; Wen, Xiaohong; Gao, Yuanhui; Huang, Denggao; Cao, Hui; Peng, Yanling; Guo, Na; Ni, Jie; Zhang, Shufang (Frontiers in Cell and Developmental Biology, 2021)
Bladder cancer is a common malignant tumor of the urinary system. Despite recent advances in treatments such as local or systemic immunotherapy, chemotherapy, and radiotherapy, the high metastasis and recurrence rates, especially in muscle-invasive bladder cancer, have led to the evaluation of more targeted and personalized approaches. A fundamental understanding of the tumorigenesis of bladder cancer along with the development of therapeutics to target processes and pathways implicated in bladder cancer has provided new avenues for the management of this disease. Accumulating evidence supports that the tumor microenvironment (TME) can be shaped by and reciprocally act on tumor cells, which reprograms and regulates tumor development, metastasis, and therapeutic responses. A hostile TME, caused by intrinsic tumor attributes (e.g., hypoxia, oxidative stress, and nutrient deprivation) or external stressors (e.g., chemotherapy and radiation), disrupts the normal synthesis and folding process of proteins in the endoplasmic reticulum (ER), culminating in a harmful situation called ER stress (ERS). ERS is a series of adaptive changes mediated by unfolded protein response, which is interwoven into a network that can ultimately mediate cell proliferation, apoptosis, and autophagy, thereby endowing tumor cells with more aggressive behaviors. Moreover, recent studies revealed that ERS could also impede the efficacy of anti-cancer treatment including immunotherapy by manipulating the TME. In this review, we discuss the relationship among bladder cancer, ERS, and TME; summarize the current research progress and challenges in overcoming therapeutic resistance; and explore the concept of targeting ERS to improve bladder cancer treatment outcomes.